Win some, lose some: The ecophysiology of Porites astreoides as a key coral species to Caribbean reefs - Lima, Lais F.O.; Bursch, Hayden; Dinsdale, Elizabeth A. (Frontiers in Marine Science, 2022)
Caribbean reefs have undergone large-scale losses in coral cover in past decades, sparking a search for species that are resilient under stress. Porites astreoides has been considered a “winner” and a key player in sustaining coral cover in the Caribbean as more sensitive species struggle. However, P. astreoides has recently declined in abundance, raising concern about its status as a winner. Here, we reviewed the ecophysiology of P. astreoides in response to environmental stress to elucidate whether this species could thrive in the future of Caribbean reefs. We examined ecophysiological variables of P. astreoides related to photosynthesis, growth, recruitment, tissue condition, and microbiome in response to temperature, pH, macroalgal competition, depth, and sedimentation. Overall, P. astreoides was sensitive to environmental stress and each physiological feature showed varying levels of sensitivity. Coral-algal photosynthesis and coral tissue condition could withstand single events of thermal stress but reflected a metabolic imbalance that hinders recovery from repeated bleaching events, compromising long-term success. Colony growth was particularly vulnerable to low pH and macroalgal competition. Recruitment was unaffected, or even favored, by depth and could tolerate high temperatures, but it was sensitive to exposure to macroalgae, especially in combination with abiotic stressors. The response of the microbiome of P. astreoides to stressors is still poorly understood. In relation to other corals, P. astreoides was frequently reported as the most sensitive species in the reviewed literature. The success of P. astreoides is tightly integrated into the future of Caribbean reefs, which could be losing an old winner.